Numerical and experimental investigation of the interaction of natural and propagated hydraulic fracture - Fatahi, Hassan; Hossain, Mofazzal; Sarmadivaleh, Mohammad (Elsevier Inc., 2017)
Hydraulic fracturing is extensively used to develop unconventional reservoirs, such as tight gas, shale gas and shale oil reservoirs. These reservoirs are often naturally fractured. Presence of these natural fractures can have beneficial or detrimental effects on the outcome of hydraulic fracturing operation. A proper study is required to characterize these formations, and design a suitable hydraulic fracturing operation. This paper investigates the interaction of hydraulic and natural fractures based on numerical and experimental studies. Distinct Element Method (DEM) based numerical model has been used to simulate interaction of hydraulic and natural fractures; and the simulation results are validated through experimental studies. The experimental results are found to be in very good agreement with simulation results. The study demonstrated that the Distinct Element Method based numerical model can be used as an alternative to laboratory experiments to investigate the interaction mechanisms of hydraulic and natural fractures with greater confidence. Both experimental and numerical simulation tests showed that increasing the angle between plane of natural fracture, and direction of maximum horizontal stress increases the chance of hydraulic fracture to cross the natural fractures. At low angles, hydraulic fracture is most likely to be arrested at the plane of natural fracture; and/or cause a shear slippage at the plan of natural fracture. Natural fracture filling materials also have a great effect on the interaction mechanism. Weakly bonded natural fracture surfaces increase the chance of shear slippage to occur, and arrest the propagation of hydraulic fracture even at the high angle of interaction as high as 90°.